Producción científica de enfermeras egresadas de la Universidad de Antioquia. Relaciones salud y sociedad, Colombia, 1980-1990 (1996)
ABSTRACT: This article is the summary of a wider study that tries to give a global viw from the social medicine scope of the nurses’ researches done during the period of 1980-1990. This was done by using the content analysis of 44 research studies on the subjects studied, the referential theoretical approach, the concepts and the categories, the coherence, the techniques and the procedures for the analysis and the contributions to health and the profession in the Province of Antioquia. Moreover, the quantitative analysisi of the 78 research studies were concluded.